Un incontro sulla psicoterapia di gruppo nelle istituzioni - Vari, Autori (Il sogno della farfalla, 2018)
The article discusses the research into group psychotherapy being carried out by a number of authors in a meeting held at the University of Chieti. The different experiences reported all have the therapist’s training as a common denominator: the “collective analysis”, a particular group psychotherapy which has been conducted by Massimo Fagioli for the last 35 years, whose historical precedent can be identified in a practice carried out in the psychiatric hospital of Padova in 1962. Starting from an article which appeared in those years written by Fagioli, the authors propose that group psychotherapy in the institutions be based on three fundamental concepts: setting, transfert and interpretation. This inalienable methodology must operate within a framework of theoretical principles that reject the idea that mental illness can be neither identified nor cured and argues that its origins lay in non-conscious interhuman relations. The authors, moreover, recognize how fundamental it is for the psychiatrist in his therapeutic work to have a medical identity, traditionally linked exclusively to the body’s biological dimension. Only when we are able to overcome the scission between psychiatry and psychotherapy, anchoring the latter to a medical context and removing it from its destiny of offering support and consolation can we look for a cure to mental illnes.